2002
DOI: 10.1088/0953-4075/35/4/304
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution investigations of C2and CN optical emissions in laser-induced plasmas during graphite ablation

Abstract: Graphite ablation in low-pressure nitrogen atmosphere has been carried out by XeCl excimer laser radiation at the fluence of 12 J cm-2. The induced-plasma plume has been investigated by time- and space-resolved emission spectroscopy. The recorded spectra are dominated by diatomic molecule bands: the C2 Deslandres-D'Azambuja and Swan systems and the CN violet system. From experimental measurements, it turns out that the continuum, the atomic emissions and the C2 Deslandres-D'Azambuja bands are predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…The vibrational temperature is the maximum at a most efficient laser fluence of 287 J cm −2 . These results are consistent with earlier reports on vibrational temperature by different authors [11,13,18,20,22,28,30]. It has been observed [7] that the degree of the diamond-like character in DLC films varies due to different temperatures in the laserinduced plasma.…”
Section: The Calculation Of the Vibrational Temperaturesupporting
confidence: 92%
“…The vibrational temperature is the maximum at a most efficient laser fluence of 287 J cm −2 . These results are consistent with earlier reports on vibrational temperature by different authors [11,13,18,20,22,28,30]. It has been observed [7] that the degree of the diamond-like character in DLC films varies due to different temperatures in the laserinduced plasma.…”
Section: The Calculation Of the Vibrational Temperaturesupporting
confidence: 92%
“…For two background N 2 gas molecules, the corresponding values are the same few millimeters and ϳ 5 s. The CN * emissions observed in the nanosecond PLA studies are seen to maximize at x ϳ 5 mm-as observed by others also. [32][33][34] The apparent propagation velocities of the CN * emitters are comparable to those deduced for the emitting C + ions and C neutrals, but about an order of magnitude faster than those of the observed C 2 ͑d͒ radicals.…”
Section: Discussionsupporting
confidence: 61%
“…This technique with temporal resolution has been used by many researchers to investigate the graphite ablation plume. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The wavelength and spatially resolved measurements of emission spectra of the CO 2 laser ablation plume at the carbon target have been reported recently by us. 26,27 The present paper is aimed at discussing thermochemical processes produced by a high-power IR CO 2 pulsed laser on graphite target and at evaluating laser ablation induced changes, which are of fundamental importance in establishing the mechanisms responsible for the plasma emission.…”
Section: Introductionmentioning
confidence: 99%